A dream EEG and mentation database - Wong, William; Herzog, Rubén; Andrade, Katia Cristine; Andrillon, Thomas; de Araujo; Draulio Barros; Arnulf, Isabelle; Ataei, Somayeh; Avvenuti, Giulia; Baird, Benjamin; Bellesi, Michele; Bergamo, Damiana; et al. (NATURE PORTFOLIO, 2026)
Magneto/electroencephalography (M/EEG) studies of dreaming are an essential paradigm in the investigation of neurocognitive processes of human consciousness during sleep, but they are limited by the number of observations that can be collected per study. Dream research also involves substantial methodological and conceptual variability, which poses problems for the integration of results. To address these issues, here we present the DREAM database-an expanding collection of standardized datasets on human sleep M/EEG combined with dream report data-with an initial release comprising 20 datasets, 505 participants, and 2643 awakenings. Each awakening consists, at minimum, of sleep M/EEG ( >= 20 s, >= 100 Hz, >= 2 electrodes) up to the time of waking and a standardized dream report classification of the subject's experience during sleep. We observed that reports of conscious experiences can be predicted with objective features extracted from EEG recordings in both Rapid Eye Movement (REM) and non-REM (NREM) sleep. We also provide several examples of analyses, showcasing the database's high potential in paving the way for new research questions at a scale beyond the capacity of any single research group.